UJI COBA TES POTENSI AKADEMIK MAHASISWA: ASSEMBLY TEST COGNITIVE - Siti Nurhaliza; Salsabila Abdullah; Tarisa Fahriah; Dhiya Rachma Kintani; Ima Halimatusa’diah (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2026)
Academic potential tests are psychological assessment tools used to identify an individual’s cognitive abilities in order to predict their chances of success in higher education. Generally, academic potential tests in Indonesia consist of three ability subtests: verbal, quantitative, and reasoning. The purpose of this study was to construct and test the item analysis of an academic potential test for students in the Faculty of Psychology at Buana Perjuangan Karawang, class of 2022, in order to obtain an instrument that meets psychometric criteria and is suitable for use a measure of students’ academic ability. The result of this study indicate that the majority of test items possess satisfactory discriminant validity, with 20 items effectively distinguishing respondents’ ability levels among the 26 participants. The study employed a descriptive quantitative design using incidental sampling. Analysis of the instrument’s difficulty revealed that it was dominated by ideal items with p-values ranging from 0.31 to 0.70. Additionally, 19 items demonstrated good distractor effectiveness because Xdis < Xbar or had values ≥ 0.025, and the Spearman-Brown reliability coefficient reached 0.90. These values indicate a very high level of internal concictency, exceeding the minimum acceptable reliability threshold of 0.70. Academic potential tests are psychological assessment tools used to identify an individual’s Tes potensi akademik merupakan alat ukur psikologis yang dimanfaatkan untuk mengidentifikasi kemampuan kognitif individu dalam memperkirakan peluang keberhasilan dalam belajar di perguruan tinggi. Umumnya tes potensi akademik di Indonesia terdiri dari tiga subtes kemampuan, yaitu terdiri dari subtes verbal, kuantitatif, serta penalaran. Tujuan dari penelitian ini yaitu untuk mengkonstruksi serta menguji analisis aitem tes potensi akademik pada mahasiswa Fakultas Psikologi Universitas Buana Perjuangan Karawang angkatan 2022 sehingga diperoleh instrumen yang memenuhi kriteria psikometrik dan layak digunakan sebagai alat ukur kemampuan akademik mahasiswa. Adapun hasil dari penelitian ini menunjukan bahwa mayoritas butir soal memiliki kualitas daya diskriminasi yang memuaskan, di mana ada 20 aitem yang dapat membedakan tingkat kemampuan responden secara baik pada 26 partisipan. Kemudian desain penelitian ini menggunakan kuantitatif deskriptif dengan teknik sampling insidental. Dari hasil analisis kesukaran instrumen ini didominasi dengan aitem ideal dengan nilai p berada pada rentang 0,31 hingga 0,70 dan sebanyak 19 aitem efektivitas distraktor kategori baik karena Xdis < Xbar atau nilai ≥ 0,025 serta memiliki nilai koefisien reliabilitas Spearman-Brown yang mencapai angka 0,90. Nilai tersebut menunjukkan tingkat konsistensi internal yang sangat tinggi dari batas minimal reliabilitas yang diterima sebesar 0,70.